Challenges Humanitarian Aid Professionals Face Working with Unaccompanied Minors in Mexico - Parra-Sánchez, Harumi; Gordon, Sarah Frances; Polanco Hernández, Graciela; Turnbull, Bernardo; Vidal de Haymes, María (Frontera Norte, 2024)
This study explores the experiences of humanitarian aid professionals working with unaccompanied migrant minors in Mexico. Using a qualitative research design, the authors conducted semi-structured interviews with eight of these professionals (three men and five women), ages 30 to 45. Reflexive thematic analysis was employed to decipher the rich narratives from the interviews. The findings of this study reveal the significant stress experienced by humanitarian aid workers in this context, shedding light on the coping strategies adopted to manage the psychological strain inherent to their roles. In addition to these insights, this study reveals key thematic elements encompassing these professionals’ perspectives on the migrant crisis and the challenges faced in their work.